A ratiometric electrochemical biosensor for glycated albumin detection based on enhanced nanozyme catalysis of cuprous oxide-modified reduced graphene oxide nanocomposites. Issue 45 (28th October 2021) - Li, Zhi; Zhang, Jingwen; Dai, Ge; Luo, Feifei; Chu, Zhaohui; Geng, Xing; He, Pingang; Zhang, Fan; Wang, Qingjiang
Abstract : A ratiometric electrochemical biosensor based on enhanced nanozyme catalysis of cuprous oxide-modified reduced graphene oxide nanocomposites was developed and applied in the determination of glycated albumin in the blood serum of diabetic mice. Abstract : Nanozymes have enzyme-like characteristics and nanozyme-based electrochemical sensors have been widely studied for biomarker detection. In this work, cuprous oxide-modified reduced graphene oxide (Cu2 O–rGO) nanozyme was prepared by simultaneous reduction of copper chloride and graphene oxide. This Cu2 O–rGO nanozyme displayed an outstanding electrocatalytic activity to glucose oxidation and was used as the modified material of a glassy carbon electrode to fabricate an electrochemical ratiometric biosensor for glycated albumin (GA) detection. In this ratiometric biosensor, methylene blue-labeled DNA tripods (MB-tDNA) were adsorbed on the Cu2 O–rGO/GCE surface to form a bioinspired electrode (MB-tDNA/Cu2 O–rGO/GCE), in which the catalytic sites of Cu2 O–rGO were covered by MB-tDNA. In the presence of target GA, GA could be identified by the aptamer sequence contained in MB-tDNA, and a MB-tDNA/GA complex was formed and released into the solution, so the reduced current of MB-tDNA was decreased. Simultaneously, the oxidized current of the outer added glucose was increased since more catalytic sites of Cu2 O–rGO nanozyme on the substrate electrode surface were exposed. The ratio of the peak currents of glucose oxidation and methylene blue reduction ( I Glu / I MB ) was used to monitor the GA level and ultimately improve the accuracy of the method. The electrochemical sensor showed a low detection limit of 0.007 μg mL −1 and a wide linear range from 0.02 to 1500 μg mL −1 . The proposed sensor was also successfully used to measure the GA expression level in the blood serum of a diabetic mouse model.